Regorafenib overcomes chemotherapeutic multidrug resistance mediated by ABCB1 transporter in colorectal cancer: In vitro and in vivo study. (28th June 2017) - Wang, Yi-Jun; Zhang, Yun-Kai; Zhang, Guan-Nan; Al Rihani, Sweilem B.; Wei, Meng-Ning; Gupta, Pranav; Zhang, Xiao-Yu; Shukla, Suneet; Ambudkar, Suresh V.; Kaddoumi, Amal; Shi, Zhi; Chen, Zhe-Sheng
Abstract: Chemotherapeutic multidrug resistance (MDR) is a significant challenge to overcome in clinic practice. Several mechanisms contribute to MDR, one of which is the augmented drug efflux induced by the upregulation of ABCB1 in cancer cells. Regorafenib, a multikinase inhibitor targeting the RAS/RAF/MEK/ERK pathway, was approved by the FDA to treat metastatic colorectal cancer and gastrointestinal stromal tumors. We investigated whether and how regorafenib overcame MDR mediated by ABCB1. The results showed that regorafenib reversed the ABCB1-mediated MDR and increased the accumulation of [ 3 H]-paclitaxel in ABCB1-overexpressing cells by suppressing efflux activity of ABCB1, but not altering expression level and localization of ABCB1. Regorafenib inhibited ATPase activity of ABCB1. In mice bearing resistant colorectal tumors, regorafenib raised the intratumoral concentration of paclitaxel and suppressed the growth of resistant colorectal tumors. But regorafenib did not induce cardiotoxicity/myelosuppression of paclitaxel in mice. Strategy to reposition one FDA-approved anticancer drug regorafenib to overcome the resistance of another FDA-approved, widely used chemotherapeutic paclitaxel, may be a promising direction for the field of adjuvant chemotherapy. This study provides clinical rationale for combination of conventional chemotherapy and targeted anticancer agents. Highlights: Regorafenib reverses the ABCB1-mediated multidrug resistance in vitro and in vivo . Regorafenib inhibits the efflux activity of ABCB1 transporter. Regorafenib and paclitaxel synergistically shrink resistant colorectal tumors. Regorafenib does not induce cardiotoxicity/myelosuppression of paclitaxel in mice.